Super Simple Chemistry - Mani Ramaswamy Ed (Great Britain Dorling Kindersley Ltd, 2020)
A fantastic aid for course work, homework, and test revision, this completely comprehensive guide to key stages 3 and 4, and the entire GCSE curriculum, makes Chemistry crystal clear and will have you exam-ready in no time. Each topic is fully illustrated to support the information, make the facts crystal clear and bring the science to life. A large central image explains the idea visually and each topic is summed up on a single page, helping children to quickly get up to speed and really understand how Chemistry works. Information boxes explain the theory with the help of simple graphics. And for revision, a handy "key facts" Box provides a simple summary you can check back on later. With clear, concise coverage of all the core topics, super simple Chemistry is the perfect accessible guide to Chemistry for children, supporting classwork, and making studying for exams The easiest it's ever been.
Keywords: The Ultimate Bitesize Study Guide; Key Stages 3-4; Smart Materials; Chemistry of the Earth